Sources of financial and credit support for the innovation sector of Kazakhstan (Journal of Economic Research & Business Administration, 2019)
The development of the innovation sector is an important task of the economic policy of any state. In Kazakhstan, certain measures to form an effective model of innovative development of the economy are being taken, the amount of funding for the innovation sector is increasing annually. At the same time, in this area, problems of imperfection of the current regulatory framework, lack of favorable conditions for conducting innovation activities of enterprises, low availability of financial and credit resources, etc., remain. Needs of innovation sector entities in significant investment and credit resources necessitate finding new approaches to attraction of investments, formation of an effective system of financing the innovation sphere, which determines the relevance of the research topic. The purpose of the study is to conduct a comprehensive study of existing financial and credit sources of financing the innovation sector in the Republic of Kazakhstan and assess their impact on the development of the innovation sector. The article identifies the strengths and weaknesses, threats and opportunities of the existing system of financing the innovation sector, identifies areas for its improvement. Based on the application of regressionanalysis, the article investigates the possible change in the volume of exports of high-tech goods underthe influence of such sources of financial and credit support as the costs of research and development,bank lending, foreign investment, and the investment potential of the pension and insurance sectors. Theresults of the study showed that the volume of export of high-tech products is significantly affected by thecosts of R&D, bank loans to the private sector, assets of the pension and insurance sectors. The methodologicalapproaches outlined in this study can be used by government agencies in developing targetedprograms and measures for financial support for the innovation sector. The results of the study can alsobe used in the activities of financial and credit organizations for the further development of relationshipswith enterprises of the innovation sector of the economy